PENGARUH MEDIA PEMBELAJARAN INTERAKTIF BERBASIS DIGITAL TERHADAP HASIL BELAJAR SISWA DI KELAS V SD NEGERI 060938 MEDAN - Resta Marbun; Anton Sitepu; Frikson Jony Purba; Eka Kartika Silalahi; Irmina Pinem; Patri Janson Silaban (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of using interactive digital-based learning media on the learning outcomes of fifth-grade students at SDN 060938 Medan in the 2024/2025 academic year. This research employed a quantitative method, with the study population consisting of all fourth-grade students at SDN 060938. The research sample comprised 28 students selected through purposive sampling techniques. Data on the use of interactive digital-based learning media were obtained through questionnaires distributed to students, while learning outcomes were measured using students' pretest and posttest scores during the 2024/2025 academic year. The results of this study indicate that student learning outcomes using the The use of interactive digital based learning model fall into the